2017
DOI: 10.1038/s41598-017-17327-9
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of signallers can maintain sexual signal variation under stabilizing selection

Abstract: How sexual communication systems can evolve under stabilizing selection is still a paradox in evolutionary biology. In moths, females emit a species-specific sex pheromone, consisting of a blend of biochemically related components, to which males are attracted. Although males appear to exert strong stabilizing selection on female pheromone, these blends seem to have evolved rapidly, as evidenced by ~120,000 moth species. Here we propose and test a “proximity model” wherein two females that vary in their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Interestingly, these two processes co- Schwander et al (2010) occur at comparable scales in forest tent caterpillar (Lepidoptera: Lasiocampidae) (Evenden et al, 2015). In moths, proximity of calling females has been hypothesized to enhance the mating success of both attractive and unattractive females (van Wijk et al, 2017). However, empirical observations suggest the reverse: at a small scale, mating probability of females tends to decline with the number of conspecifics (Shiga, 1977;references in Rhainds, 2010), suggestive of intrasexual competition among females for access to males.…”
Section: Signal Interference and Natural Mating Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these two processes co- Schwander et al (2010) occur at comparable scales in forest tent caterpillar (Lepidoptera: Lasiocampidae) (Evenden et al, 2015). In moths, proximity of calling females has been hypothesized to enhance the mating success of both attractive and unattractive females (van Wijk et al, 2017). However, empirical observations suggest the reverse: at a small scale, mating probability of females tends to decline with the number of conspecifics (Shiga, 1977;references in Rhainds, 2010), suggestive of intrasexual competition among females for access to males.…”
Section: Signal Interference and Natural Mating Disruptionmentioning
confidence: 99%
“…Natural mating disruption (high rates of FMF on crowded host plants) can arise due to: (1) males being unable to discriminate receptive females from conspecific males or non receptive females (Richerson et al, 1976;Takeuchi, 2017;Sales et al, 2018), (2) passive olfactory signals of post reproductive conspecifics interfering with mate location (Gwynne & Lorch, 2013;Rhainds, 2018), or (3) adsorption of pheromone onto the foliage of host plants (Noldus et al, 1991). Testing these hypotheses requires small-scale mapping of female mating probability among georeferenced plants (van Wijk et al, 2017;Muniz et al, 2018;Sciarretta et al, 2018).…”
Section: Signal Interference and Natural Mating Disruptionmentioning
confidence: 99%
“…If females, for example, typically only encounter a few males in sequence in the wild, it may be problematic for them to express choosiness when confronted simultaneously with two or more males in the laboratory. A recent study showed that, in the wild, female moths take advantage of staying in groups to blur male choosiness [17]. It is becoming more and more clear that what we observe in the laboratory may not actually reflect what is happening in nature [18].…”
Section: Open Accessmentioning
confidence: 67%
“…Sex pheromones can serve as attractive aggregation pheromones for females, strengthening their pheromone plumes to draw in more males from the environment and provide more choices for mates. [17][18][19] Additionally, 'satellite' noncalling females may benefit from aggregating with calling females by improving their chances of mating, taking advantage of other attractive females' plumes. 17 Since pheromone autodetection can also influence female calling behavior, it may impede the success of pheromone-mediated mating disruption.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Additionally, 'satellite' noncalling females may benefit from aggregating with calling females by improving their chances of mating, taking advantage of other attractive females' plumes. 17 Since pheromone autodetection can also influence female calling behavior, it may impede the success of pheromone-mediated mating disruption. In many lepidopteran species, females increase calling when exposed to conspecific females or synthetic sex pheromone.…”
Section: Introductionmentioning
confidence: 99%